2011
DOI: 10.1021/jp109559p
|View full text |Cite
|
Sign up to set email alerts
|

Modified Scaled Hierarchical Equation of Motion Approach for the Study of Quantum Coherence in Photosynthetic Complexes

Abstract: We present a detailed theoretical study of the transfer of electronic excitation energy through the Fenna-Matthews-Olson (FMO) pigment-protein complex, using the newly developed modified scaled hierarchical approach (Shi, Q.; et al. J. Chem. Phys. 2009, 130, 084105). We show that this approach is computationally more efficient than the original hierarchical approach. The modified approach reduces the truncation levels of the auxiliary density operators and the correlation function. We provide a systematic stud… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
164
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 127 publications
(173 citation statements)
references
References 38 publications
5
164
1
Order By: Relevance
“…To lower the temperature (β¯ω 0 ≈ 10), one may need to employ numerical techniques to accelerate calculations. [89][90][91][92] It should be noted that dynamical behavior of the system does not change so much once the temperature becomes low enough compared with the characteristic frequency of the system (such as ω u ), since the thermal excitation becomes so small that the fluctuation does not play any role for electronic excitation at very low temperature. So, in practice, we do not have to lower the temperature below β¯ω u ≈ 10 for ω 0 ω u .…”
Section: Numerical Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To lower the temperature (β¯ω 0 ≈ 10), one may need to employ numerical techniques to accelerate calculations. [89][90][91][92] It should be noted that dynamical behavior of the system does not change so much once the temperature becomes low enough compared with the characteristic frequency of the system (such as ω u ), since the thermal excitation becomes so small that the fluctuation does not play any role for electronic excitation at very low temperature. So, in practice, we do not have to lower the temperature below β¯ω u ≈ 10 for ω 0 ω u .…”
Section: Numerical Resultsmentioning
confidence: 99%
“…Inclusions of multimode are computationally very expensive, and therefore one has to employ a variety of numerical techniques developed for HEOM approach to accelerate numerical calculations. 46,47,[89][90][91][92] Here, we assumed that the primary oscillator modes are harmonic. However, if we employ a less reduced density matrix in which the bath (x n j ) modes are eliminated and we still keep the oscillator coordinates q j , we can relax this limitation.…”
Section: Discussionmentioning
confidence: 99%
“…Non-Markovian effects from the environment can also be added to the quantum Liouville equation (for example, refer to Ref. [10]); however, they will not qualitatively change the effect of strong electron correlation within chromophores on energy-transfer efficiency.…”
Section: B Environmental Effectsmentioning
confidence: 99%
“…Recent spectroscopic experiments [1][2][3] and theoretical models [4][5][6][7][8][9][10][11][12][13], provide evidence that efficient light harvesting in nature occurs by a quantum mechanism involving sustained electronic coherence [14] and entanglement [15,16] between chromophores. While the chromophores are chlorophyll molecules containing large networks of conjugated carbon bonds that surround a charged magnesium ion, they have largely been represented in theoretical studies [4][5][6][7][8][9][10][11][12][13] by one-electron models that neglect the effects of electron correlation and entanglement within chromophores. Two advanced methods in electronic structure, density-matrix renormalization group [17] and two-electron reduceddensity-matrix theory [18,19], have recently shown that networks of conjugated bonds as in acene chains [17,20], acene sheets [20], and chlorophyll are associated with polyradical character that cannot be adequately described without a strongly correlated many-electron quantum model.…”
Section: Introductionmentioning
confidence: 99%
“…To tackle this problem, a methodology referred to as hierarchical equation of motion (HEOM) has been developed by Tanimura and co-workers [19,20]; a high temperature approximation (HTA) of HEOM has also been developed by Ishizaki and co-workers to describe the EET dynamics in a model dimer [21,22]. The HEOM has already been implemented in calculating the excitonic transfer dynamics of photosynthetic proteinpigment complexes [23][24][25][26][27] and more recently it is also used within simulations of the linear and 2D electronic spectra of the above mentioned systems [28][29][30].…”
Section: Introductionmentioning
confidence: 99%